2017
DOI: 10.4149/km_2017_1_57
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cryogenic treatment on ageing behaviour of B4C reinforced 7075 aluminium composites

Abstract: In the current study, an effect of cryogenic treatment on the ageing of a B4C particulate reinforced 7075 aluminium alloy was investigated to identify changes in hardness with respect to ageing time. To achieve this, first, 10, 15, and 25 % by weight B4C particulate containing 7075 Al composite specimens were produced by hot pressing of Al, Cu, Zn, and Mg elemental powders. Next, cryogenic treatment and multiple steps of tempering were adapted to several samples. Such as, after solutionizing at 470• C and sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Being now in a meta-stable condition, solid solubility of the alloy is further reduced with decreasing the cryogenic temperature [36]. Thus, for the present material, it is possible to speculate under what condition partial super saturation of the solute elements occurs, where ultra-ne nodules of precipitate of phase (Mg 2 Al 3 ) emerge, particularly along the sub-grain boundary lines.…”
Section: Microstructurementioning
confidence: 90%
See 2 more Smart Citations
“…Being now in a meta-stable condition, solid solubility of the alloy is further reduced with decreasing the cryogenic temperature [36]. Thus, for the present material, it is possible to speculate under what condition partial super saturation of the solute elements occurs, where ultra-ne nodules of precipitate of phase (Mg 2 Al 3 ) emerge, particularly along the sub-grain boundary lines.…”
Section: Microstructurementioning
confidence: 90%
“…It has been recently noticed that during cryogenic cooling, alloying elements, such as Mg and Cu, become increasingly dense and ne throughout the matrix [36]. Particularly, ageing process right after cryogenic treatment yields Mg and Cu agglomeration at several zones, initially indicating coarse Mg-and Cu-rich zones that are getting ner and so homogenously distributed within the matrix.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that cryogenic treatment could improve the mechanical properties of aluminum alloy. Taskesenet al [10] analyzed the effect of CTT on the ageing behaviour of Al 7075-B4C composites. The hardness of the cryogenically-treated specimens increases considerably.Kumar et al [11] analyzed the impact of DCT on the wear rate of AISI D3 Die Steel using statistical tools.…”
Section: Iintroductionmentioning
confidence: 99%
“…Low cost, lightness, resistance against corrosion, good ductility and aesthetic appearance are the most crucial properties of the Al alloys. Due to these properties, research of these alloys has been undergoing in the academic field and the potential for commercialization of these alloys has increased [1].…”
Section: Introductionmentioning
confidence: 99%